KAJIAN TEORI ICEBERG DALAM MEMBACA - Adiana, Meilia (Jurnal Pengembangan Pendidikan, 2011)
Abstract. Reading iscommon activity. Some people think that reading is only to kill our time or toget additional information. The process of comprehension a text seems so simplebut, in fact, it is a very complicated process. The knowledge or informationthat the readers get happens is a long process but in a very rapid movement(saccadic movement). The iceberg on the surface appears small as words that thereaders see. In a second those words are sent to out brain, as itâs called thedeep, to be processed. Some components work and the result is the comprehensionof the text.Â Keyword : iceberg, saccadic movement